Influence of Digital Loan Applications on Loan Performance of Microfinance Banks in Kenya - Waweru, Faith Waithira; Mwaniki, Gillian; Rintari, Nancy (International Journal of Professional Practice, 2026)
Microfinance banks play a critical role in promoting financial inclusion by serving underserved populations. However, the sector continues to experience high levels of non-performing loans, which stood at 32.9% as of 30 June 2023. This has prompted many microfinance banks to adopt digital innovations, such as digital loan applications, to improve loan performance. The objective of this study was to examine the influence of digital loan applications on the loan performance of microfinance banks in Kenya. The study adopted an ex post facto research design guided by the pragmatism research philosophy. The target population comprised 348 loan officers drawn from the 13 licensed microfinance banks in Kenya. Proportionate stratified sampling was used to determine the sample size. Both primary and secondary data were utilized in the study. Primary data were collected using semi-structured questionnaires, while qualitative data were analyzed using thematic analysis. Quantitative data were analyzed using descriptive and inferential statistics with the aid of SPSS version 28. Descriptive statistics included means and standard deviations, whereas inferential statistics comprised Pearson correlation and logistic regression analysis. The findings revealed that digital loan applications had a strong and statistically significant positive relationship with loan performance (r = 0.695, p < 0.05). Regression results further established that digital loan applications significantly and positively influenced loan performance among microfinance banks in Kenya (β = 3.884, p < 0.05), leading to the rejection of the null hypothesis. Qualitative findings indicated that the ease of access to digital lending increases the risk of borrower over-indebtedness, as clients often obtain multiple loans from different platforms with minimal assessment of repayment capacity, thereby increasing default rates. The study recommends that microfinance banks enhance their digital loan platforms to support seamless applications, faster approvals, timely disbursements, user-friendly interfaces, and accessible customer support services.